2020
DOI: 10.3390/ijerph17165760
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Forgiveness, Gratitude, and Self-Control on Reactive and Proactive Aggression in Bullying

Abstract: The social cognitive approach to moral development posits that moral self-schemas encourage character strengths and reduce adolescents’ aggression. However, limited research has examined the influence of positive personal characteristics on proactive behaviors and reactive aggression in bullying. This study examined direct and mediational relationships between forgiveness, gratitude, self-control, and both proactive and reactive aggression in bullying. The extent to which the structural relations of this model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 120 publications
3
9
0
8
Order By: Relevance
“…For example, gratitude and affective empathy that resembles abovementioned positive emotions, promote actions that benefit others even at a cost to the self (Lishner, Steinert, & Stocks, 2016). In addition, gratitude is often described as a protective factor that fosters positive functioning (e.g., proactive coping, life satisfaction, well-being, positive beliefs, creativity and altruistic behaviors), and minimizes the risk of psychopathology (e.g., reactive and proactive aggression, suicidal ideation and behaviors, depression and anxiety, traumatic symptoms) (Vernon, Dillon, & Steiner, 2009;Israel-Cohen, Florina, Kashy-Rosenbaum, & Kaplan, 2015;Van Dusen, Tiamiyu, Kashdan, & Elhai, 2015;Arnout & Almoied, 2020;García-Vázquez, Valdés-Cuervo, & Parra-Pérez, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, gratitude and affective empathy that resembles abovementioned positive emotions, promote actions that benefit others even at a cost to the self (Lishner, Steinert, & Stocks, 2016). In addition, gratitude is often described as a protective factor that fosters positive functioning (e.g., proactive coping, life satisfaction, well-being, positive beliefs, creativity and altruistic behaviors), and minimizes the risk of psychopathology (e.g., reactive and proactive aggression, suicidal ideation and behaviors, depression and anxiety, traumatic symptoms) (Vernon, Dillon, & Steiner, 2009;Israel-Cohen, Florina, Kashy-Rosenbaum, & Kaplan, 2015;Van Dusen, Tiamiyu, Kashdan, & Elhai, 2015;Arnout & Almoied, 2020;García-Vázquez, Valdés-Cuervo, & Parra-Pérez, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Con el primer objetivo se pretendió examinar las correlaciones entre la gratitud, la IE y la ciberagresión. De acuerdo a las evidencias de la literatura previa (Cañas et al, 2019;Chen et al, 2020;García-Vázquez et al, 2020;Geng, 2018;Preś et al, 2020;Yudes et al, 2020), los resultados de este estudio mostraron correlaciones significativas entre las tres variables en las direcciones esperadas. Así, se ha observado que aquellos adolescentes con un mejor desarrollo de las competencias emocionales muestran una mayor conciencia sobre las cosas positivas que experimentan en su vida cotidiana.…”
Section: Discussionunclassified
“…Con el segundo objetivo se analizan las relaciones de ambos recursos con la ciberagresión. Considerando hallazgos previos sobre el papel protector de la IE en el ciberacoso (p.ej., Carbonell y Cerezo, 2019; Yudes et al, 2020) y de la gratitud sobre las actitudes y los comportamientos agresivos (p.ej., Chen et al, 2020;García-Vázquez et al, 2020), se espera encontrar que ambos recursos expliquen, de manera independiente, una disminución de la conducta ciberagresiva. En el tercer y último objetivo, se pretende explorar el papel moderador de la IE en la relación entre gratitud y ciberagresión.…”
Section: Objetivos Del Presente Estudiounclassified
See 1 more Smart Citation
“…One of the traits associated with bullying is moral disengagement, which is linked to apathy or indifference to bullying-related actions, whether from a bystander or an aggressor (Bandura, 2016;de Oliveira et al, 2019). In addition, moral disengagement in bullying cases has been related to low scores in consideration of others and poor self-control (García-Vázquez et al, 2020). In this line, a longitudinal study by Thornberg et al (2019) including elementary students revealed that changes in moral disengagement altered the bullying behavior and increased the collective efficacy of the class, which stopped aggression towards other students.…”
Section: Introductionmentioning
confidence: 99%